Phylogenetic Analysis and Genome-Wide Association Study Applied to an Italian Listeria monocytogenes Outbreak - Chiaverini, Alexandra; Guidi, Fabrizia; Torresi, Marina; Acciari, Vicdalia Aniela; Centorotola, Gabriella; Cornacchia, Alessandra; Centorame, Patrizia; Marfoglia, Cristina; Blasi, Giuliana; Di Domenico, Marco; Migliorati, Giacomo; Roussel, Sophie; et al. (Frontiers in Microbiology, 2021)
From May 2015 to March 2016, a severe outbreak due to Listeria monocytogenes ST7 strain occurred in Central Italy and caused 24 confirmed clinical cases. The epidemic strain was deeply investigated using WGS analysis. In the interested area, the foodborne outbreak investigation identified a meat food producing plant contaminated by the outbreak strain, carried by pork- ready to-eat products. In the same region, in March 2018, the epidemic strain re-emerged causing one listeriosis case in a 10-months-old child. The aim of this study was to investigate the phylogeny of the epidemic and re-emergent strains over time and to compare them with a closer ST7 clone, detected during the outbreak and with different PFGE profiles, in order to identify genomic features linked to the persistence and the re-emergence of the outbreak. An approach combining phylogenetic analysis and Genome Wide Association Study (GWAS) revealed that the epidemic and re-emergent clones were genetically closer to the ST7 clone with different PFGE profiles and strictly associated to the pork production chain. The repeated detection of both clones was probably correlated to (i) the presence of truly persistent clones and the repeated introduction of new ones (ii) the contribution of prophage genes in promoting the persistence of the epidemic clones. Despite no significant genomic differences were detected between the outbreak and the re-emergent strain, the two related clone detected during the outbreak can be differentiated by transcriptional factor and phage genes associated to the phage LP-114.